2017
DOI: 10.1111/mms.12458
|View full text |Cite
|
Sign up to set email alerts
|

Variability in blue whale acoustic behavior off southern California

Abstract: To evaluate the acoustic behavior of blue whales (Balaenoptera musculus) located inshore and offshore of southern California, singular A and B calls, D calls, and AB phrases were analyzed from 12 mo of passive acoustic data collected at four locations within the Southern California Bight. The relative proportions of singular calls and phrases were used to evaluate spatial and temporal patterns in sound and song type usage, and singular call and phrase production rates were calculated to investigate spatial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Visual inspection of the tag records revealed that many dives made by individuals of both species during the circuits of offshore waters had the characteristics of dives made while whales are vocalizing (shallow, flat-bottomed, minimal acceleration; see Calambokidis et al, 2007;Oleson et al, 2007;Stimpert et al, 2015). Additionally, it has been suggested that the better acoustic propagation properties of offshore waters (Sirovic et al, 2015) make them advantageous for reproductive calls (Lewis and Sirovic, 2018). Thus, we speculate these circuits in southern California waters by males of both species were related to reproduction, although we caution that this is based on a rather small number of individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual inspection of the tag records revealed that many dives made by individuals of both species during the circuits of offshore waters had the characteristics of dives made while whales are vocalizing (shallow, flat-bottomed, minimal acceleration; see Calambokidis et al, 2007;Oleson et al, 2007;Stimpert et al, 2015). Additionally, it has been suggested that the better acoustic propagation properties of offshore waters (Sirovic et al, 2015) make them advantageous for reproductive calls (Lewis and Sirovic, 2018). Thus, we speculate these circuits in southern California waters by males of both species were related to reproduction, although we caution that this is based on a rather small number of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-based differences in acoustic behavior have been documented for both blue and fin whales, with most of the more complex vocal repertoire of each species being produced exclusively by males and believed to be related to reproduction, while singular calls are produced by both sexes in the context of foraging (Croll et al, 2002;Oleson et al, 2007;Stimpert et al, 2015;. Further, spatial variability in the type and rate of calling has been documented in blue whales off southern California, suggesting there may be spatial separation of behavioral activities (Lewis and Sirovic, 2018), although a lack of direct observation makes the underlying process unclear, as both feeding and reproductive calls are recorded throughout the feeding season in southern California (Lewis and Sirovic, 2018). Considering that animals in southern California waters are exposed to a variety of regional stressors like ship strikes (Berman-Kowalewski et al, 2010;Redfern et al, 2013) and anthropogenic sound (Goldbogen et al, 2013;DeRuiter et al, 2017), a potential spatial segregation arising from behavioral differences between sexes could lead to disproportionate impacts (Sprogis et al, 2016) over short temporal scales (Pirotta et al, 2018) or on long-term population fitness (Pirotta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These variable down-swept calls appear to be commonly produced by different blue whale populations [ 44 , 45 ] and are probably used as social calls while foraging [ 33 ]. D calls are typically recorded in southern California from April to November, peaking during the summer [ 33 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike stereotyped calls, their time-frequency shape and duration are highly variable, and their occurrence is sporadic. D-calls have been recorded in the presence of blue whales in the Pacific [1], [8] and in the Atlantic [9], of Antarctic blue whales [10], [11] and of three acoustic populations of pygmy blue whales in the Indian Ocean [12]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Easier to detect automatically, stereotyped calls are commonly used to monitor blue whale sub-species and population presence and migrations. Yet, the presence of blue whales in the Pacific has been attested by the occurrence of D-calls, whilst no stereotyped calls were detected [8], [15]. Besides, D-calls appear in the behavioral context of foraging [7], whereas songs are thought to be a reproductive display.…”
Section: Introductionmentioning
confidence: 99%